Effects of Bacillus subtilis A-5 and its fermented γ-polyglutamic acid on the rhizosphere bacterial community of Chinese cabbage - Bai, Naling; Zhang, Hanlin; He, Yu; Zhang, Juanqin; Zheng, Xianqing; Zhang, Haiyun; Zhang, Yue; Lv, Weiguang; Li, Shuangxi (Frontiers in Microbiology, 2022)
Chemical fertilizer reduction combined with novel and green agricultural inputs has become an important practice to improve microecological health in agricultural production. Given the close linkages between rhizosphere processes and plant nutrition and productivity, understanding how fertilization impacts this critical zone is highly important for optimizing plant–soil interactions and crop fitness for agricultural sustainability. Here, by using a pot experimental system, we demonstrated that nitrogen fertilizer reduction and microbial agent application promoted plant fitness and altered the microbial community structure in the rhizosphere soil with the following treatments: no fertilization, CK; conventional chemical fertilizer, CF; 30% reduced nitrogen fertilizer, N; 30% reduced nitrogen fertilizer with pure γ-PGA, PGA; 30% reduced nitrogen fertilizer with Bacillus subtilis A-5, A5; 30% reduced nitrogen fertilizer with γ-PGA fermentation broth, FJY. The PGA, A5, and FJY treatments all significantly promoted crop growth, and the FJY treatment showed the strongest positive effect on Chinese cabbage yield (26385.09 kg/hm2) (P<0.05). Microbial agents affected the α diversity of the rhizosphere bacterial community; the addition of B. subtilis A-5 (A5 and FJY treatments) significantly affected rhizospheric bacterial community structure. Urease activity and soil pH were the key factors affecting bacterial community structure and composition. The FJY treatment seemed to influence the relative abundances of important bacterial taxa related to metabolite degradation, predation, and nitrogen cycling. This discovery provides insight into the mechanism underlying the effects of microbial agent inputs on rhizosphere microbial community assembly and highlights a promising direction for the manipulation of the rhizosphere microbiome to yield beneficial outcomes.